1989
DOI: 10.1007/bf02535075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of omega‐3 fatty acids on vascular smooth muscle cells: Reduction in arachidonic acid incorporation into inositol phospholipids

Abstract: A rapid increase in arachidonic acid incorporation into phosphatidylinositol (PI) occurred following exposure of cultured porcine pulmonary artery smooth muscle cells to calcium ionophore A23187. This response was specific for PI and phosphatidic acid; none of the other phosphoglycerides showed any increase in arachidonic acid incorporation. The incorporation of [3H]inositol also was increased, indicating that complete synthesis of PI rather than only fatty acylation occurred in response to the ionophore. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
1
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 43 publications
0
6
1
1
Order By: Relevance
“…Compared to findings at basal calcium concentrations, we did not observe any effect of fish oil intake on thrombin-induced changes in intracellular free calcium. This finding is in contrast to in vitro results of Yerram and Spector [40] who observed a decrease in agonist-stimulated intracellular free calcium after incubation of vascular smooth muscle cells with fish oil.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Compared to findings at basal calcium concentrations, we did not observe any effect of fish oil intake on thrombin-induced changes in intracellular free calcium. This finding is in contrast to in vitro results of Yerram and Spector [40] who observed a decrease in agonist-stimulated intracellular free calcium after incubation of vascular smooth muscle cells with fish oil.…”
Section: Discussioncontrasting
confidence: 56%
“…It has also been suggested that its blood pressure lowering effects might be due to an altered production of vasoactive prostaglandins [7,23,28]. Fish oil might alter the composition of the plasma membrane of vascu-629 lar smooth muscle cells and thus influence phosphoinositide metabolism with a concomitant alteration in intracellular calcium regulation [40,41]. Since platelets have been used as a model to study intracellular calcium regulation in patients with essential hypertension, and several authors have found that intracellular free calcium is increased in hypertensive patients [11,12,13,24], we investigated the effects of fish oil on basal and stimulated intracellular free platelet calcium.…”
Section: Discussionmentioning
confidence: 99%
“…Since increased intake of -3 polyunsaturated fatty acids has been associated with decreased levels of arachidonic acid incorporation into the phospholipid pool of vascular smooth muscle and endothelium, we speculated that this would lead to decreased formation of arachidonic acid metabolites in the kidney (31,32). We observed a slight decrease in arachidonic acid epoxygenase activity in renal cortical microsomes from DHA-fed rats.…”
Section: Discussionmentioning
confidence: 65%
“…It has been proposed that the hypotensive properties of fish oil may result from changes in eicosanoid metabolism (13). Vascular smooth muscle and endothelial cells have been shown to incorporate -3 polyunsaturated fatty acids at the expense of -6 polyunsaturated fatty acids (31,32). The subsequent reduction in arachidonic acid limits endogenous synthesis of vasoactive eicosanoids such as the potent vasoconstrictor TXA 2 (14).…”
Section: Discussionmentioning
confidence: 99%
“…Altering the lipid composition of mem branes can affect the activity of membranebound enzymes and receptor functions and overall metabolic functions [28]. Both EPA and DHA are incorporated into vascular membranes [29] which increases membrane fluidity and flexibility resulting in decreased peripheral vascular resistance [30], Structural alterations in the membrane occur with aging such that membrane receptor density de creases and fluidity is reduced due to changes in the content of membrane phospholipids and cholesterol [28], Age-related decreases in the following, in cluding F344 rat aortic (Na,K)ATPase activi ty [31], active Ca2+ uptake activity of sarco plasmic reticulum (SR) vesicles from rat myo cardium [32], P2-purinergic receptor activity [3.3], and NE-activated initial efflux response in F344 rat aortic [34] have been docu mented. Interestingly, Ca-ATPase activity in cardiac SR is reduced following fish oil feed ing in mice [35].…”
Section: Discussionmentioning
confidence: 99%